1984
DOI: 10.1093/sjaf/8.3.123
|View full text |Cite
|
Sign up to set email alerts
|

Dimension Lumber Grade and Yield Estimates for Yellow-Poplar

Abstract: Equations that predict the dimension lumber grade yield from yellow-poplar trees (Liriodendron tulipfera L.) and sawlogs that are manufactured into 2 x 4's using the Saw-Dry-Rip system are presented. These equations require the measurement of dbh and merchantable height measured to an 8-in. top diameter. To predict the dimension lumber yield from yellow-poplar logs, a grading system that incorporates limiting defects with the clear-face concept used in southern pine log grading is utilized to stratify the logs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Defects, such as knots, stains, knobs, and holes, as well as the length and diameter of logs, are the main variables that impact lumber yields (Denig et al 1984;Kretschmann 2010). Lumber yields can be predicted using only the diameter and length of the log, but the log quality is perhaps the most important and major factor for predicting the log yield.…”
Section: Hardwood Log Gradesmentioning
confidence: 99%
“…Defects, such as knots, stains, knobs, and holes, as well as the length and diameter of logs, are the main variables that impact lumber yields (Denig et al 1984;Kretschmann 2010). Lumber yields can be predicted using only the diameter and length of the log, but the log quality is perhaps the most important and major factor for predicting the log yield.…”
Section: Hardwood Log Gradesmentioning
confidence: 99%
“…This process, now tried on numerous low-and medium-density hardwoods, has proved to be eminently successful. Extensive study of yellow-poplar studs at several locations has shown 90 to 100 percent of pieces manufactured by SDR to be of STUD grade (Denig and Wengert 1985;NHPMA 1978;. Results for other species such as paper birch , red alder (Layton 1982), and cottonwood (Trachsel 1982) have been very good, as have limited trials on basswood, red maple, black willow , sweetgum, blackgum, and sycamore.…”
Section: Structural Lumber From Aspen: Using the Saw-dry-rip (Sdr) Prmentioning
confidence: 99%
“…Assessing the yield and recovery of SGHL is crucial for determining SGHL's economic feasibility as a CLT raw material. Previous yield studies by Denig et al (1984), Koch andStenglein (1986), andAllison et al (1987) focused on specific methods and species and aimed to produce SGHL for different markets than CLT, so a comprehensive evaluation is necessary to align with current market dynamics and sawing technology. However, Azambuja et al (2022) studied to produce SGHL for the structural market by remanufacturing the NHLA grade lumber focusing on CLTs, which likely cost more and become less competitive in the current market.…”
Section: Introductionmentioning
confidence: 99%